EVALUASI WAKTU TUNGGU PELAYANAN RESEP PASIEN RAWAT JALAN DI INSTALASI FARMASI RSUD Dr. R. SOEDJONO SELONG - Deasi Wikandari; Mahmuluddin (Universitas Kristen Immanuel, 2021)
Waiting time is the time used by patients to get prescription services. The length of time the patient waits can reflect how the hospital manages the service component that is tailored to the patient's situation and expectations. This observation was carried out to find out the waiting time for concoction and non-concoction prescription services in outpatient BPJS patients at the Dr. General Hospital Pharmacy Installation. R. Soedjono Selong and find out what factors influence the prescription waiting time in the Pharmacy Installation of the Regional General Hospital Dr. R. Soedjono Selong. The sample observed was a recipe for concoction and non- concoction which had been determined by the criteria for taking data by using Data Retrieval Sheets (LPD). Regional Dr. R. Soedjono Selong has provided maximum service to health services, especially servants of recipes for concoction and non-concoction medicines. The average waiting time required for working on a prescription at the Regional General Pharmacy Pharmacy Dr. R. Soedjono Selong is 54 minutes for concoction drugs and 29 minutes for non- concoction drugs. Thus, the waiting time for concoction and non-concoction recipe services has an average waiting time that does not exceed prescription service standards based on the Decree of the Minister of Health of the Republic of Indonesia Number: 129/Menkes/ SK/II/2008.